Class Action Research Report Efforts To Improve Class IV Science Learning Outcomes Trought The Numbered Heads Learning Strategytogether At State 1 Tulas Primary School Academy Year 2020/2021 - Kurniawati, Etik (Universitas Sebelas Maret, 2022)
This research aims to increase understanding of science learning material about energy using the Numbered Heads Together (NHT) learning method for class IV students. The form of this research is classroom action research using a cycle model. Each cycle consists of four stages, namely: planning, implementation, action, observation and reflection. As a sample, there were 9 students in class IV semester II of SD Negeri 1 Tulas, consisting of 4 male students and 5 female students. The implementation of improvement research was carried out in 2 cycles. Based on the results of the research on learning outcomes, it can be concluded that the implementation of cycle I showed an increase in learning outcomes. The scores of students who reached the KKM or completed were 3 (33.33%) students out of 9 students before improvements were made and experienced an increase of 22.22% or 5 (55.55%) students who completed out of 9 students. Meanwhile, student activity is still lacking. Meanwhile, in cycle II, there was also an increase of 100% of students completing or reaching the KKM and student activity scores getting a good average score. In this way, recommendations for using the Numbered Heads Together (NHT) learning method can improve student results regarding energy in class IV semester II students. SD Negeri 1 Tulas, Karangdowo District, Klaten Regency, 2020/2021 Academic Year.